PENGATURAN PEMANFAATAN SUMBER DAYA ALAM LAUT DAN PESISIR BERBASIS PENEGAKAN HUKUM DAN KEADILAN - Aguw, Youla Olva (Universitas Sam Ratulangi, 2013)
Youla Olva Aguw. The Regulation and The Utilization of Marine Natural Resources And Coastal Based On Law Enforcement And Justice. Purpose of this study were To know the reality of the regulation and management of marine natural resources and coastal, and to know the ideal concept of the regulation, management and utilization marine natural resources marine and coastal to promote the rights of communities in marine and coastal areas. This research is a normative laws are more focused on efforts to find a concept the regulation of marine natural resources and coastal, the authority of the institution in , management, and the existence of coastal communities . 1)The reality of regulation and utilization marine natural resources and the coastal current is the disharmonisation in legislations between sectors, bertween levels of government and across regions, disharmony in the implementation of the authority of the institutions associated with regulation and utilization of marine natural resources and coastal both levels of government and between regions . 2) The concept of the ideal in the regulation and management of marine naturral resources and coastal is to harmonize of egulation with humanistic and ecological approach (green regulation), to harmonize the authority of the institutions involved in the management of marine resources and coastal with integrative approach (green management ), empowers indigenous people with digging through a participatory approach (greeen community) as well as the consistency and commitment of business actors with partnership approach (green investment). The whole concept is referred to as The holistic and proportionate concept in natural resource management and marine) using a 7 (seven) approach of reference, respect, restrain, redistribution, realible, responsibility and regeneration. Keywords: Natural Resources, fair and law enforcement